A new species of the genus Heligmonevra Bigot, 1858 (Diptera, Asilidae) from Indian Himalaya with a revised key to its species. (2nd January 2019) - Naskar, Atanu; Maity, Aniruddha; Banerjee, Dhriti
Abstract: A new species of Heligmonevra Bigot, 1858 is described and illustrated from Neora Valley National Park, presently in Kalimpong district of West Bengal, India. The new species, Heligmonevra paruii sp. n. is differentiated from its closely related species Heligmonevra cheriani (Joseph & Parui, 1980) by a J-shaped hook-like projection of lower lobe of epandrium with a row of setae at upper border, in comparison to slightly curved epandrium at apex with row of spines at upper border in H. cheriani . With this new addition the genus Heligmonevra Bigot, 1858 is now represented by 20 species from India. An identification key to all known Indian species is also provided. http://zoobank.org/urn:lsid:zoobank.org:pub:2CB66D37-999F-4954-9208-5DD179C37B5E